Nanoscale zero-field electron spin resonance spectroscopy - Fei Kong (Nature Portfolio, 2018)
Demonstrations of sensing devices using nitrogen vacancy centres have shown significantly improved sensitivity compared to traditional methods. Here the authors demonstrate an approach for performing nanoscale electron spin resonance without magnetic fields in order to achieve better spectral resolution.